2009
DOI: 10.1017/s0317167100007198
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Infective Endocarditis Caused by C. Hominis in a Patient with HLAB27 Aortitis

Abstract: A 59-year-old, right handed, Caucasian engineer presented to the emergency department 12 hours after the sudden onset of left sided weakness and numbness. The patient had been in good health until the year prior to admission. He had an episode of bilateral ankle swelling with cough, pleuritic chest pain and night sweats 12 months prior to admission. Six months later he had left ankle swelling and left foot drop, followed by right knee soreness and swelling a month later, and swelling of the left calf and right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…C. hominis is also known to cause large friable vegetations complicated by systemic embolism [11] . Therefore, we reviewed cases of systemic embolism caused by C. hominis IE ( Table 2 ) [5] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] . 21 cases of C. hominis IE associated with embolism, including the present case, have been reported since 1980.…”
Section: Discussionmentioning
confidence: 99%
“…C. hominis is also known to cause large friable vegetations complicated by systemic embolism [11] . Therefore, we reviewed cases of systemic embolism caused by C. hominis IE ( Table 2 ) [5] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] . 21 cases of C. hominis IE associated with embolism, including the present case, have been reported since 1980.…”
Section: Discussionmentioning
confidence: 99%
“…Almost one-half of patients require valve replacement. Peripheral and central nervous system emboli occur frequently in C hominis endocarditis, noted in 51% and 21% of cases, respectively, especially when the aortic valve is involved ( 3 , 5 , 6 ). Extravascular infection is unusual ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the relationship of C. hominis with endocarditis. [34567] The identification of C. hominis is well established with the Vitek ® 2 compact identification system.…”
Section: Discussionmentioning
confidence: 99%